Pengembangan Media Permainan Ular Tangga untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas III SDN 3 Gumulan - Kristanti, Rini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to develop a snake and ladder game media to improve the learning out comes of elementary school students.This research is development research this research use smet a analysis method. One of the problems of education is the lack of media facilities and infrastructure, so teachers are required to be creative in improving the quality of learning in the classroom, such as developing learning media in the classroom. One of the interesting learning media that can overcome student boredom in learning activities is game-based learning activities, such as the application of snakes and ladders game media. In student learning outcomes, it shows that 35% of students have scores above the KKM before applying the snake and ladder learning media, while after applying the snake and ladders learning media, 95% of students have scoresabove theKKM (Minimum Completeness Criteria), it shows student learning outcomes an increase of 60. The use of learning media in learning activities makes it easierfor students to gain understanding and motivate students to learn.